Pemecahan Masalah Matematika Kontekstual Siswa Kelas IX SMP pada Materi SPLDV Ditinjau dari Self-Efficacy - Ayu Sukma Pradana; Masriyah Masriyah (Universitas Negeri Surabaya, 2026)
Problem-solving is a critical skill in mathematics education. This qualitative study employed a case study approach to examine how ninth-grade students with high, moderate, and low self-efficacy solve contextual problems involving System of Linear Equations in Two Variables. Three students representing different self-efficacy levels were selected through purposive sampling. Data were collected using a self-efficacy questionnaire, a mathematics ability test, problem-solving tasks, and interviews. Data analysis was based on self-efficacy questionnaire scores, mathematics ability test results, problem-solving indicators proposed by Mason et al. (2010), and reduction of interview data to explore students' problem solving. The findings revealed no differences in problem-solving performance between students with high and moderate self-efficacy. At the entry stage, they identified relevant information, determined goals and methods, stated the problem requirements, and made assumptions. At the attack stage, they solved the problems correctly but did not provide logical reasoning. At the review stage, they rechecked their answers and solution steps and reflected on difficulties encountered, but could not identify other problems solvable using the same method. In contrast, the student with low self-efficacy showed differences at all stages. The student recorded incomplete information, made numerous calculation errors, lacked logical reasoning, did not recheck solution steps, was uncertain about the answers, and could not identify similar solvable problems. These findings suggest that mathematics teachers should strengthen students’ self-confidence, reasoning, calculation accuracy, and reflective habits to support effective problem-solving.